Evaluation of Atrial Septal Defect Using Real-time Three-dimensional Echocardiography： Comparison with Surgical Findings - Mweri, Saumu Tobbi; Deng, Youbin; Cheng, Peixuan; Lin, Hanhua; Wang, Hongwei; Mkangara, Ommari Baaliy; Xia, Zhi; Hu, Xiufen; Bi, Xiaojun; Wu, Yuhan; Bapumiia, Mustaafa; Shentu, Weihui; et al. (Journal of Huazhong University of Science and Technology. Medical sciences, 2009)
The present study evaluated the application of three dimensional echocardigraphy （3DE） in the diagnosis of atrial septal defect （ASD） and the measurement of its size by 3DE and compared the size with surgical findings. Two-dimensional and real-time three dimensional echocardiography （RT3DE） was performed in 26 patients with atrial septal defect, and the echocardiographic data were compared with the surgical findings. Significant correlation was found between defect diameter by RT3DE and that measured during surgery （r=0.77, P〈0.001）. The defect area changed significantly during cardiac cycle. Percentage change in defect size during cardiac cycle ranged from 6%-70%. Our study showed that the size and morphology of atrial septal defect obtained with RT3DE correlate well with surgical findings. Therefore, RT3DE is a feasible and accurate non-invasive imaging tool for assessment of atrial septal size and dynamic changes.